Is the acute surgical unit model feasible for Australian regional centres?. Issue 11 (31st August 2016) - Shilton, Hamish; Tanveer, Amin; Poh, Benjamin Ruimin; Croagh, Daniel; Jayasuriya, Neil; Chan, David
Abstract : Background: A significant proportion of general surgery emergency procedures are conducted after‐hours in regional centres. The acute surgical unit (ASU) model reduces the number of after‐hours operations performed. We review the burden of emergency surgery in a regional centre and assess what components of the ASU model would benefit regional hospitals. Methods: Retrospective analysis was performed on data for all emergency cases performed at Latrobe Regional Hospital (LRH) over a 1‐year period. Time into and out of theatre was used to determine total theatre usage and if the operation occurred after‐hours. ED triage time to theatre and start time for appendicectomy was compared to data from our metropolitan referral hospital, Monash Medical Centre (MMC), which has employed an ASU. Results: General surgery emergency cases in regional areas are regular and predictable with a median of two emergency cases performed, and a mean theatre time of 156 min per day at LRH. On weekdays, 43.1% ( n = 503) of emergency cases were done in the evening (18.00–24.00 hours), compared to 20.3% ( n = 217) on weekends when an emergency theatre is available during the day. LRH performed more appendicectomies after‐hours than MMC over a 1‐year period. Conclusion: Regional centres have a significant burden of general surgery emergency procedures; of which the number performed after‐hours is comparable to metropolitan centres. The number of procedures and theatre time required by these cases justify a dedicated emergency theatre in‐hours similar to metropolitan ASU models and this would reduce emergency operating after‐hours.